Вербальный анализ моделей бизнес-процессов - Ельчанинов, Дмитрий Борисович; Байда, К. Е. (НТУ "ХПИ", 2012)
Предложены количественные и качественные критерии сравнения моделей бизнес-процессов, построенных по методологии IDEF0. Рассмотрены основные этапы вербального анализа таких моделей (порядковая классификация, упорядочение, парное сравнение) и их ранжирование вербально-количественным методом аналитической иерархии.

Quantitative and qualitative criteria of comparison of business processes models constructed on IDEF0 methodology are proposed. The main stages of the verbal analysis of such models (order classification, ordering, pair comparison) and their ranging by a verbal-quantitative method of analytical hierarchy are considered.
Verbal analysis of business-processes models
Keywords: бизнес-процессы; методологии IDEF0; вербальный анализ; аналитическая иерархия; business-processes; IDEF0; verbal analysis; analytic hierarchy